Cell type-specific differences in β-glucan recognition and signalling in porcine innate immune cells. Issue 1 (January 2015) - Baert, Kim; Sonck, Eva; Goddeeris, Bruno M.; Devriendt, Bert; Cox, Eric
Highlights We explored the contribution of CR3 and dectin-1 in β-glucan recognition in pigs. As in humans, CR3 is the most important β-glucan receptor in porcine neutrophils. Macrophages utilise a more diverse receptor to recognise β-glucans. Focal adhesion kinase acts as a master switch regulating β-glucan-mediated responses. We discuss these findings in comparison with β-glucan receptors in mice and man.